EFFECTIVENESS OF ECO-ENZYME DOSAGE ON THE GROWTH OF POTATO PLANTLET CUTTINGS (Solanum tuberosum L.) OF THE GRANOLA KEMBANG VARIETY - Mei Ryan Sandi; Safrizal (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
This study aims to determine the effectiveness of various doses of eco-enzyme on the growth of Granola Kembang potato (Solanum tuberosum L.) plantlets. The study was conducted at the Screen House of the Kutagadung Horticultural Seed Center, Berastagi, Karo Regency, from December 2017 to January 2018. A completely randomized design (CRD) was used with four eco-enzyme dose treatments: 0 mg/L (control), 70 mg/L, 150 mg/L, and 250 mg/L, each repeated three times. The parameters observed included plant height, number of leaves, and leaf area. The data were analyzed using analysis of variance (ANOVA) and followed by a 5% DMRT test. The results showed that eco-enzyme application had a significant effect on the growth of potato planlets. The 150 mg/L dose produced the best growth in all parameters, with an average plant height of 12.84 cm, 10.23 leaves, and a leaf area of 36.77 cm². The 250 mg/L dose was not significantly different from the 150 mg/L dose, but it was higher than the control. It can be concluded that the 150 mg/L dose is the optimum dose for the growth of Granola Kembang potato planlets.